Fourier ptychographic microscopy for extended focus range with conjugated optics. (June 2020) - Lim, Jinsang; Choi, Guk-Jong; Choi, Hyun; Park, No-Cheol
Highlights: Configuration of Fourier ptychographic microscopy with extended focus range is proposed. Conjugation mirror is introduced to extend focus range. Proposed method provides a wide field of view with high resolution and extended focus range. It is validated by measuring the change in resolution over a focus range of ±2 mm using the United States Air Force chart. It is experimentally verified by measuring a volumetric sample. Abstract: We propose a configuration of Fourier ptychographic microscopy (FPM) to modulate the focus to a large extent. FPM is widely used to obtain high-resolution images in a wide field of view. A conjugation mirror with an axially scannable mirror is introduced to conventional FPM to extend the focus range. The proposed FPM provides a wider field of view with higher resolution compared to general microscopy using the same numerical aperture. In addition, it can measure a wider focus range. Therefore, it is expected to be applied to volumetric samples more easily compared to FPM. The proposed technique is validated by measuring resolution while moving the United States Air Force resolution chart up to ± 2 mm in the axial direction and experimentally verified by measuring a volumetric sample with a depth of 4 mm created using bead with 1 μm of diameter.